Diseño e implementación de páginas web, para la organización muebles Arteco (2011)
Nowadays, to design and implementing web services and web portals a previous analysis is required in order to accomplish them. This analysis is based on users’ necessities since these systems are created for people like administrative assistants of companies and their clients. Therefore, taking into account that these users are accustomed to use the same web portals to work and to be updated, it would be inappropriate provide them new systems which will be difficult to manage by them. In accordance with the last statement, it was created a useful tool called “content’ managers” (CMS) in order to facilitate the web pages’ handling and surfing to inexperience users.